CHILDREN AND THE EARTH ON WHICH WE LIVE (bagaimana membelajarkan konsep Bumi dan Jagad raya pada anak usia SD) - Kurniyatul Faizah (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2017)
Earth is one of the planets among the other planets in the solar system arrangement of the galaxy Bima Sakti which enables the existence of a life. The life of living creatures (plants, animals and humans) can last for generations on earth in a chain cycle involving relationships between biotic and abiotic elements. Earth is made up of rocks, ¾ is waters, others are made up of soil, air which surrounds it is called the atmosphere, the condition of the waters, the soil, and the atmosphere is necessary to know, the uniqueness of the solar system and the existence of life on earth. Minerals and rocks, waters, oceans, atmosphere, and energy from the sun are very important for life.In studying of earth and the universe it is very difficult for children to introduce the theoretical concept of the earth, but it is still possible to do a learn activity to introduce the concept of the earth to children with various experiments that may be done by the children. The perception of the earth that has been built in the minds of children will be proved in the contextual learning process with a pleasant learning atmosphere. Such learning process is expected to facilitate the learning process of children and bring the impression that learning is not a dull one.The purpose of writing this article is as an effort to provide alternative reference in learning about the concept of the earth and the natural surroundings in children by utilizing the surrounding environment that may be reached by children in conducting investigation, observation and other activities that are closely related to learning about the earth and the natural surroundings. This paper is still far from perfect, therefore there needs to be a joint reflection to make improvements in an effort to improve the quality of learning, especially in learningscience in elementary school.